Act of a literary hero in literature theory and history - Tatiana V. Shvetsova, Nikolay I. Nikolaev, (Opción, 2019)
This article presents a theoretical re-evaluation of the act of a literary hero concept and its historical and literary content via the review and critical assessment of contemporary works dedicated to the theory of the hero’s act. As a result, the act of a literary hero can be used as a formal characteristic helping to distinguish the participants in the plot of the literary work. In conclusion, we believe that the described approach to studying literary heroes through the prism of their acts brings in some fundamentally new elements to understanding the logic of the historical literary process.